Penerapan Dzikir Yaumiyah Dalam Pembinaan Akhlak Santri Di Pondok Pesantren Misdad - Marsum Marsum; Moh. Farah Ubaidillah; Muchlis Muchlis (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of dzikir yaumiyah in fostering the moral development of santri at Pondok Pesantren Misdad, as well as to assess its impact on the formation of religious character. Employing a descriptive qualitative approach, the study involved interviews, observations, and document analysis. The findings indicate that dzikir yaumiyah is implemented in a structured manner through the habituation of daily worship practices, post-prayer remembrance (dzikir), and the recitation of Ratib al-Haddad and Ratib al-Attas as routine afternoon activities for the santri. In the morning, the santri recite Wirdul Lathif, Hizib Nawawi, and Wirid Syakron, in addition to other forms of wirid, accompanied by spiritual guidance from the Pengasuh (Abuya) and ustaz. These practices have a significant influence on the formation of religious character, such as discipline, inner peace, humility (tawadhu’), and obedience in worship. Dzikir yaumiyah thus serves as an effective method of moral development as it integrates spiritual, emotional, and behavioral aspects.